ANALYSIS OF RESERVOIR ROCK CHARACTERISTICS AND DETERMINATION OF DIAGENESIS USING PETROGRAPHIC DATA FROM WELL SA-09 IN THE BEKASAP FORMATION, CENTRAL SUMATRA BASIN - Ditania, Ayu
This study analyzes the reservoir characteristics of well SA-09 in the Bekasap Formation, Central Sumatra Basin, to determine the depositional environment, diagenesis, and provenance using petrographic data. The analysis reveals three main facies associations: delta plain, marsh, and delta front. The delta front facies (interval 5251-5254 feet) consists of massive mudstone to very fine sandstone with laminations and convolute laminations, dominated by Quartz Sublitharenite and Calcareous Quartz Subarkose, indicating good reservoir potential. The marsh facies (interval 5247.65-5251 feet) contains mudstone and very fine sandstone with carbonaceous material, showing more variable reservoir potential with lower porosity and permeability. The delta plain facies (interval 5224-5247.65 feet) consists of mudstone to very coarse sandstone with flaser, cross-lamination, and ripple lamination structures, reflecting variations in current energy that affect porosity and permeability distribution, indicating very good reservoir potential. Diagenetic processes including eogenesis and mesogenesis play a significant role in determining reservoir quality. Eogenesis results in initial structures and primary porosity, while mesogenesis leads to mineral changes and cementation that affect vertical porosity and permeability. Dolomite and ankerite cementation can significantly reduce porosity and permeability to 2.3% - 18.6% and 0.57 mD - 18.5 mD, respectively. However, their presence in well SA-09 is not extensive enough to impact reservoir quality. Provenance analysis indicates that most of the material originates from the stable craton interior with a long sedimentation history, while some comes from recycled orogenic sources with a more complex deformation history. The implications are that the lower part of the reservoir has good quality with high permeability, the middle part shows poor quality, and the upper part has better quality compared to delta front and marsh. This study provides an in-depth understanding of the relationship between depositional environment, diagenesis, and provenance on reservoir quality, which is important for hydrocarbon exploration and management in the Central Sumatra Basin.